2012
DOI: 10.1002/jcu.21887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of finger joint synovial vascularity in patients with rheumatoid arthritis using contrast‐enhanced ultrasound with water immersion and a stabilized probe

Abstract: PURPOSE.: To assess synovial microvascularity in finger joints with rheumatoid arthritis (RA) by contrast-enhanced ultrasound (CEUS), distinguishing between cases of active disease and those in remission; to standardize the technique for software analysis. METHODS.: Fifty-two finger joints of RA patients (26 with active disease and 26 in remission) were immersed in water and examined by CEUS using a fixed probe. Signal intensity curves were calculated with the software. RESULTS.: Contrast enhancement was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
1
24
1
1
Order By: Relevance
“…Even with the recent advancement of musculoskeletal ultrasonography such as wideband Doppler imaging, spatial compound imaging, extended field of view imaging and elastographic imaging, there are still great needs to improve the diagnostic potential of ultrasonography for small musculoskeletal lesions 10, 34, 37-39. Microbubble contrast agents have been commonly used to enhance the contrast in intravascular ultrasonography and have recently been employed for musculoskeletal ultrasonography 13-15. In this regard, we sought to establish whether H 2 O 2 -triggered bubble-generating PVAX nanoparticles could serve as ultrasound contrast agents for skeletal muscle and tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the recent advancement of musculoskeletal ultrasonography such as wideband Doppler imaging, spatial compound imaging, extended field of view imaging and elastographic imaging, there are still great needs to improve the diagnostic potential of ultrasonography for small musculoskeletal lesions 10, 34, 37-39. Microbubble contrast agents have been commonly used to enhance the contrast in intravascular ultrasonography and have recently been employed for musculoskeletal ultrasonography 13-15. In this regard, we sought to establish whether H 2 O 2 -triggered bubble-generating PVAX nanoparticles could serve as ultrasound contrast agents for skeletal muscle and tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Microbubble contrast agents are limited to microcirculation or vascularity and abdominal regions including liver, pancreas and kidney 12. Microbubbles are also unable to extravasate to reach muscle and tendon injuries because of poor tissue penetration 13-15. Moreover, microbubbles have insufficient stability because perfluorocarbon gas expands at body temperature and diffuses away through the defects of stabilizing shells 16.…”
Section: Introductionmentioning
confidence: 99%
“…[21] For better stability, finger joints were immersed in the water during CEUS examinations in some researches. [25]…”
Section: Methods Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…A multicenter study of the International Arthritis Contrast Ultrasound Study Group (IACUS) showed that CEUS was able to improve the differentiation of active synovitis from inactive intra-articular thickening [3]. In a previous study, we demonstrated the elevated sensitivity and specificity of CEUS in distinguishing active disease from remission in rheumatoid arthritis [4]. Drug treatment of cutaneous psoriasis and PsA consisted of non-steroidal anti-inflammatory drugs (NSAIDs), local or systemic corticosteroids (CSs) and diseasemodifying anti-rheumatic drugs (DMARDs).…”
Section: Introductionmentioning
confidence: 94%
“…The US probe was immersed in the water and fixed 10 mm above the joint using a special bracket. This set up allowed a focus at synovial level avoiding artefacts due to movements, joint incongruity and inhomogeneous gel application as previously described [4]. A contrast bolus injection (4.8 mL) followed by bolus of 20 mL saline solution 0.9% was executed on the opposite arm.…”
Section: Ceusmentioning
confidence: 99%